Preparation of micro-wrapped pyrite-ceramsite fillers for enhancing advanced nitrogen and phosphorus removal in sulfur autotrophic denitrification processes - Cong Ding; Bolin Li; Hongyun Hu; Xiang Li; Xiang Chen; Yingying Yan; Rui Ni; Changying Pei (Journal of Water Process Engineering, 2026)

Corrigendum to “Preparation of micro-wrapped pyrite-ceramsite fillers for enhancing advanced nitrogen and phosphorus removal in sulfur autotrophic denitrification processes” [J. Water Process Eng. 92 (2026) 110648] - Cong Ding; Bolin Li; Hongyun Hu; Xiang Li; Xiang Chen; Yingying Yan; Rui Ni; Changying Pei (Journal of Water Process Engineering, 2026)

Impact of argillaceous sediment consolidation on groundwater quality evolution: new insights from numerical simulations of porewater and solute release - Wenkai Qiu; Yao Du; Teng Ma; Wenhui Liu; Yetong Liu; Xiaochuang Bu; Bolin Zheng; Ziqi Peng; Cong Xiao; Qiwei Huang (Journal of Hydrology, 2026)

Highly efficient degradation of sulfamethoxazole by peroxydisulfate activated with phosphoric acid-modified biochar-supported copper sulfide: Performance, mechanisms, and potential applications - Weiwei Yu; Xiyin Zheng; Xi Chen; Cong Liu; Bolin Li; Lu Lv; Yuanxin Liu; Ji Li; Xinyan Li; Yan Luo; Dan Liu; Shiling Chen (Journal of Environmental Chemical Engineering, 2025)

Inhomogeneous porewater geochemistry in unconsolidated argillaceous sediments: Implications for porewater extraction protocols and characterization of solute mobilization - Wenkai Qiu; Teng Ma; Yao Du; Bolin Zheng; Ziqi Peng; Ruihua Shang; Cong Xiao; Kewen Luo; Philippe Van Cappellen (Chemical Geology, 2025)

Core-shell structured magnetic beads based on sodium alginate/chitosan for nitrogen removal enhancement - Han Zhang; Bolin Li; Cong Ding; Rui Ni; Xiangyu Lin (Chemical Engineering Journal, 2025)

Potential effects of the Emeishan large igneous province on Capitanian marine anoxia in the Upper Yangtze region - Mingzhi Kuang; Haifeng Yuan; Wenjie Li; Bolin Zhang; Chen Shen; Qinren Xiao; Xihua Zhang; Hanlin Peng; Cong Chen; Tianjun Li (Global and Planetary Change, 2024)

Evolution and adaptation of terrestrial plant‐associated Plantibacter species into remote marine environments - Li Liao; Qilong Qin; Dian Yi; Qiliang Lai; Bolin Cong; Huiming Zhang; Zongze Shao; Jin Zhang; Bo Chen (Molecular Ecology, 2024)
Microbes are thought to be distributed and circulated around the world, but the connection between marine and terrestrial microbiomes remains largely unknown. We use Plantibacter , a representative genus associated with plants, as our research model to investigate the global distribution and adaptation of plant‐related bacteria in plant‐free environments, particularly in the remote Southern Ocean and the deep Atlantic Ocean. The marine isolates and their plant‐associated relatives shared over 98% whole‐genome average nucleotide identity (ANI), indicating recent divergence and ongoing speciation from plant‐related niches to marine environments. Comparative genomics revealed that the marine strains acquired new genes via horizontal gene transfer from non‐ Plantibacter species and refined existing genes through positive selection to improve adaptation to new habitats. Meanwhile, marine strains retained the ability to interact with plants, such as modifying root system architecture and promoting germination. Furthermore, Plantibacter species were found to be widely distributed in marine environments, revealing an unrecognized phenomenon that plant‐associated microbiomes have colonized the ocean, which could serve as a reservoir for plant growth‐promoting microbes. This study demonstrates the presence of an active reservoir of terrestrial plant growth‐promoting bacteria in remote marine systems and advances our understanding of the microbial connections between plant‐associated and plant‐free environments at the genome level.

Quantitative characterization of the effect of compaction rate on ammonium release from clayey sediments - Bolin Zheng; Teng Ma; Cong Xiao; Wenkai Qiu; Ziqi Peng (Applied Geochemistry, 2024)

Systemic subchronic toxicity and comparison of four selenium nutritional supplements by 90-day oral exposure in Sprague-Dawley rats - Lu Yu; Yanmei Li; Wen Qu; Yanhua Zheng; Xuejiao Chen; Shaohua Fu; Jingjing Qu; Jie Tian; Shuiyuan Cheng; Xin Cong; Bolin Fan; Chunhong Wang (Food and Chemical Toxicology, 2023)

Synthesis of Lanthanum-Modified Attapulgite and Its Phosphorus-Fixing Mechanism for Urban Eutrophic Lake - Lingfeng Ye; Ye Li; Cong Liu; Bolin Li; Dongxue Liu; Chang Liu; Jie Wan; Chengbin Fu (Water, Air, & Soil Pollution, 2022)